Asesmen Pembelajaran pada Buku Panduan Guru dan Buku Siswa Mata Pelajaran Sejarah Kurikulum Merdeka - Ipong Jazimah; Sumiyatun Septianingsih (Keraton: Journal of History Education and Culture, 2025)
Learning assessments are carried out to interpret various kinds of information about student learning processes and outcomes. It is important to carry out assessments to see the extent of the success of learning. This research aims to reveal 1) How learning is assessed in the Teacher's Guidebook and Student's Book for history subjects in the Merdeka Curriculum. 2) What are the advantages and disadvantages of learning assessment in the Teacher's Handbook and Student's Book for history subjects in the Merdeka Curriculum. This research uses descriptive qualitative research methods with document study. Data validity is carried out by data triangulation. Data analysis uses interactive analysis with three stages of analysis, namely data reduction, data presentation, and drawing conclusions. The research results showed that the assessment used consisted of 2 forms, namely diagnostic assessment and formative assessment. Formative assessment consists of self-assessment and summative assessment. When analyzed, the assessment carried out uses operational keywords in the cognitive, affective and psychomotor domains. The advantage of the assessment used is that it is varied and explores many students' abilities to support the development of students' creativity and independence. The disadvantage of assessment is that it requires quite a lot of time to complete all the assessments carried out, so the teacher's workload also increases. Key words: learning assessment, history books, independent curriculum